Improved forearm rotation even after early conversion to below-elbow cast for non-reduced diaphyseal both-bones forearm fractures in children: a secondary 7.5-year follow up of a randomized trial - Linde Musters; Leon W Diederix; Pim P Edomskis; Kasper C Roth; Joyce L Benner; Gerald A Kraan; Jan H Allema; Max Reijman; Denise Eygendaal; Joost W Colaris (Acta Orthopaedica, 2023)
Background and purpose: previous RCT compared short-term results of above-elbow cast (AEC) with early conversion to below-elbow cast (BEC) in children with non-reduced diaphyseal both-bone forearm fractures. After 7 months both groups had comparable function. Our primary aim was to investigate whether forearm rotation improves or worsens over time. Secondary aims were loss of flexion and extension of the elbow and wrist, patient-reported outcomes measures, grip strength ratio, and radiographic assessment. Patients and methods: We performed long-term follow-up (FU) of a previous RCT. All patients were invited again for the long-term FU measurements. Primary outcome was limitation of forearm rotation. Secondary outcomes were loss of flexion and extension of the elbow and wrist compared with the contralateral forearm, the ABILHAND-Kids questionnaire and the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire, grip strength ratio, and radiographic assessment. Results: The mean FU was 7.5 (4.4–9.6) years. Of the initial 47 children, 38 (81%) participated. Rotation improved in both groups over time, with no significant difference in the final forearm rotation: 8° (SD 22) for the AEC group and 8° (SD 15) for the BEC group with a mean difference of 0° (95% confidence interval –13 to 12). Secondary outcomes showed no statistically significant differences. Finally, children < 9 years almost all have full recovery of function. Conclusion: Long-term follow-up showed that loss of forearm rotation after a non-reduced diaphyseal both-bone forearm fracture improved significantly compared with that at 7 months, independent of the initial treatment and children aged < 9 will have almost full recovery of function. This substantiates that the remaining growth behaves like a “friend” at long-term follow-up.